“I'm too old for this!”: A prospective, multilevel study of job characteristics, age, and turnover intention - Christensen, Jan Olav; Knardahl, Stein (Frontiers in Psychology, 2022)
Deciding to leave a job is often foreshadowed by burgeoning job dissatisfaction, which is in turn often attributed to characteristics of the job and work environment. However, while we know that job characteristics influence job satisfaction, health, and motivation, their associations with turnover intention is less clear. Moreover, despite ageing workforces, an understanding of how working conditions influence workers across the lifespan is lacking. Therefore, drawing on job design theories and bridging turnover- and ageing research, we studied 15 specific job characteristics to determine whether they predicted turnover intentions, and whether the predictive value was modified by age. Data were collected from various public and private enterprises in Norway. Analyses were conducted cross-sectionally (N=12485) and prospectively over two years (N=5504). Moderated multilevel regressions revealed that most work factors were associated with turnover intention at both the individual and work unit levels. A social climate of support, trust, and encouragement was most strongly inversely associated with turnover intentions, while role conflict was most strongly positively associated with turnover intentions. Organizational climate, leadership styles, and job control were more important with age while job demands and role stressors were more important to younger workers. Ten individual level- and four work-unit level factors predicted turnover intentions prospectively, suggesting turnover intentions due to poor working conditions persisted in employees that did not quit. Our results highlight several specific, modifiable job characteristics that are likely to affect turnover intentions, and the impact of certain factors specifically for older workers.